Identification of endonuclease activity in HIV-1 gp120 preparations produced using baculovirus expression systems - Davidoff, A N (BioTechniques, 1997)
Experiments undertaken with commercially available recombinantly produced human immunodeficiency virus Type 1 (HIV-1) gp120 demonstrated that the resuspended lyophilized protein, a product of the baculovirus expression system, had intrinsic nuclease activity. This nuclease activity was distinguishable from the molecular-grade bovine serum albumin that it was constituted in. The activity was thermolabile in that if the preparation was heated to 100 degrees C for 10 min, the activity was abolished, although this did not happen when it was stored at -20 degrees C. The nuclease activity was also Ca+2- and Mg+2-dependent, and had endonuclease as opposed to exonuclease activity. Zn+2 ions were found to inhibit the enzyme. The intensity of nuclease activity varied from batch to batch. A lyophilized homogenate of Sf9 insect cells expressing the Rho baculovirus-derived red blood cell protein 4.2 (Pallidin) was also found to have nuclease activity on reconstitution. In contrast, most, though not all E. coli-produced recombinant proteins were found to be free of nuclease activity. The use of activity gels to identify the size of the nuclease contained in the gp120 preparation was limited, because despite the use of many renaturation methods, the enzyme in the gp120 preparation could not be functionally resuscitated following sodium dodecyl sulfate polyacrylamide gel electrophoresis. Immunoprecipitation studies were useful to demonstrate that nuclease activity in the gp120 preparation was functionally distinguishable from the gp120 itself. When mononuclear cells transformed with anti-CD3 were concurrently incubated with gp120 (5-40 micrograms/mL), internucleosomal DNA fragments characteristic of apoptosis were demonstrated in the supernatant by DNA gel electrophoresis. In the context of HIV-1 and AIDS, where the depletion of CD4+ T-cells has been found to be associated with apoptosis, nuclease activity intrinsic to the gp120 preparation used in experimentation may potentially alter experimental results